Effects of pyrocatechol on the computational, structural, spectroscopic and thermal properties of silver-modified hydroxyapatite - Keser, Serhat; Yildiz, Aykut; Barzinjy, Azeez A.; Kareem, Rebaz Obaid; Mahmood, Bahroz Kareem; Agid, Riyadh Saeed; Bulut, Niyazi (Springer, 2025)
This study investigates the synthesis and characterization of hydroxyapatite (HAp) ceramic biomaterials doped with silver (Ag) and pyrocatechol. HAp, commonly utilized in the treatment of hard tissues including teeth and bones, was produced and analyzed to assess the structural, morphological, elemental, and thermal properties of the materials. The phase and crystal structures of the synthesized HAp biomaterials were examined using X-ray diffraction (XRD), revealing that the incorporation of Ag and pyrocatechol influenced the crystallinity and lattice parameters. Fourier transform infrared (FT-IR) spectroscopy verified the presence of the characteristic OH- and PO4(3)(-) groups of HAp, while scanning electron microscopy (SEM) displayed consistent morphologies across all samples, free of residues or impurities. Elemental compositions were determined by energy dispersive X-ray (EDX) spectroscopy, and thermal stability was assessed through differential thermal analysis (DTA) and thermogravimetric analysis (TGA). Additionally, computational studies using density functional theory (DFT) were conducted to further investigate the electronic and structural properties of 0.44% Ag-doped HAp. The DFT calculations revealed that Ag atoms replace calcium (Ca1 and Ca2) positions in the lattice, leading to slight distortions in the lattice structure and changes in the electronic density distribution. Minor changes were observed in the band structure and electronic properties, indicating the stability and tunability of the doped system. A small amount of beta-tricalcium phosphate (beta-TCP) phase was also detected alongside the main HAp phase. These results underscore the importance of incorporating pyrocatechol and silver doping into HAp for biomedical applications. The resulting biomaterials exhibit enhanced structural, thermal, and electronic properties, with improved biocompatibility and antimicrobial activity.
Keywords: Hydroxyapatite (HAp); Silver (Ag); Pyrocatechol (Pyro); Structural characterization; Thermal properties; Density functional theory (DFT)